2014
DOI: 10.1007/s00391-014-0805-8
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal sensor-based fall detection within the domestic environment of elderly people

Abstract: Current fall detection technologies work well under laboratory conditions but it is still problematic to produce reliable results when these technologies are applied to real life conditions. Acceptance towards the sensors decreased after study participation although the system was generally perceived as useful or very useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…We experienced the reality of living with a high risk of falling, rather than simply “observed” it and support the assertion that a subjective perspective in research is valuable and increases “the knowledge yield” [ 21 ]: we gained more insight than we could have through observing, evaluating, or questioning the participants anywhere other than at home. As in previous studies [ 15 ] we had some technical issues (with equipment failure and obscured sensors) and participants disclosed some concerns about surveillance but every insight gained at this stage will inform a programme of research that is now based on experience rather than supposition.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We experienced the reality of living with a high risk of falling, rather than simply “observed” it and support the assertion that a subjective perspective in research is valuable and increases “the knowledge yield” [ 21 ]: we gained more insight than we could have through observing, evaluating, or questioning the participants anywhere other than at home. As in previous studies [ 15 ] we had some technical issues (with equipment failure and obscured sensors) and participants disclosed some concerns about surveillance but every insight gained at this stage will inform a programme of research that is now based on experience rather than supposition.…”
Section: Discussionmentioning
confidence: 92%
“…Deciding where to position the minimum number of sensors capable of capturing useful data, unobtrusively, in appropriate locations requires consideration. When Feldwieser et al [ 15 ] trialled a fall-detection system in elderly people's homes, 15 falls occurred (over 1000-plus measurement days) but none within range of the Kinect sensor installed; algorithms falsely detected multiple falls every day (4592 in total); and the participants' acceptance of technology they considered “generally useful” before installation decreased with experience. To avoid some of these unwanted outcomes, we proposed a qualitative study to initiate our programme of research.…”
Section: Introductionmentioning
confidence: 99%
“…Soto-Mendoza et al [ 16 ] proposed a scheduling system for improving the lives of the elderly. Feldwieser et al [ 17 ] conducted a clinical study to detect falls and analyzed their effects and consequences with the help of a fall protocol using an accelerometer as well as optic and acoustic sensors. Kansiz et al [ 18 ] evaluated the time-domain features to determine the most discriminative features from supervised learning methods for fall detection.…”
Section: Introductionmentioning
confidence: 99%
“…In Kangas et al [ 13 ], one of the threshold-based algorithms that was in [ 9 ] was evaluated on 15 real-world falls. Finally, 12 and eight real-world falls were considered in Feldwieser et al [ 14 ] and Bloch et al [ 15 ], respectively. In addition to these, two other studies considered real-world falls for descriptive purposes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that algorithms tuned on simulated falls tend to underperform in real-life situations [ 9 , 13 , 14 ] and that simulated falls can show differences (although they also share common characteristics) with respect to real-world falls [ 16 , 17 ]. Therefore, in the present study, real-world falls and real-world ADLs are used to evaluate the performance of the proposed wavelet-based approach.…”
Section: Introductionmentioning
confidence: 99%